Acute Otitis Media in children – a review of current literature - Węgrzyn, Jan; Fijałkowski, Łukasz; Nosal, Aleksandra; Czarnecki, Adam; Galanty-Ochyra, Aleksandra; Zając, Piotr; Serwońska, Karolina; Pastuszka, Artur; Jabłońska, Olga (Journal of Education, Health and Sport, 2025)
Introduction and purpose Acute otitis media (AOM) is an infection of the middle ear, with acute onset of symptoms and signs, frequently including otalgia, fever, and otorrhea. It affects 80% of children by the age of 5 years, hence the need to collect and share current knowledge on risk factors, pathophysiology, diagnosis, treatment and complications of AOM. A brief description of the state of knowledge AOM is an extremely common infection in children, usually bacterial. Numerous risk factors lead to it, with allergies, allergic rhinitis and gastro-esophageal reflux disease being the most frequent. Inflammation within the eustachian tube causes effusion to accumulate inside the middle ear, leading to irritating symptoms. A thorough medical history and careful physical examination are used to assess, whether the patient meets obligatory criteria: acute onset of symptoms, evidence of effusion, and tympanic membrane inflammation. Observation is often sufficient, and symptoms start fading without any antimicrobials. Should this not be the case, systemic antibiotic therapy is recommended. Regardless of antibiotics, pain management is of great importance. Complications are unlikely to occur with proper diagnosis and treatment. Conclusions AOM, being a frequent condition in children, requires good knowledge on diagnostics and management to avoid as many complications as possible. Remembering possible risk factors and symptoms, both specific and less common, leads to faster diagnosis, which then decreases the risk for unnecessary pain and possible complications. Understanding the biology behind AOM together with utilization of new methods in physical examination is key to providing better care. Promising research is made on new ways to treat AOM with drug delivery systems.